Abundant Intergenic TAACTGA Direct Repeats and Putative Alternate RNA Polymerase β′ Subunits in Marine Beggiatoaceae Genomes: Possible Regulatory Roles and Origins - MacGregor, Barbara J. (Frontiers in Microbiology, 2015)
The genome sequences of several giant marine sulfur-oxidizing bacteria present evidence of a possible post-transcriptional regulatory network that may have been transmitted to or from two distantly related bacteria lineages. The draft genome of a Cand. “Maribeggiatoa” filament from the Guaymas Basin (Gulf of California, Mexico) seafloor contains 169 sets of TAACTGA direct repeats and one indirect repeat, with two to six copies per set. Related heptamers are rarely or never found as direct repeats. TAACTGA direct repeats are also found in some other Beggiatoaceae, Thiocystis violascens, a range of Cyanobacteria, and five Bacteroidetes. This phylogenetic distribution suggests they may have been transmitted horizontally, but no mechanism is evident. There is no correlation between total TAACTGA occurrences and repeats per genome. In most species the repeat units are relatively short, but longer arrays of up to 43 copies are found in several Bacteroidetes and Cyanobacteria. The majority of TAACTGA repeats in the Cand. “Maribeggiatoa” Orange Guaymas (BOGUAY) genome are within several nucleotides upstream of a putative start codon, suggesting they may be binding sites for a post-transcriptional regulator. Candidates include members of the ribosomal protein S1, Csp (cold shock protein), and Csr (carbon storage regulator) families. No pattern was evident in the predicted functions of the open reading frames (ORFs) downstream of repeats, but some encode presumably essential products such as ribosomal proteins. Among these is an ORF encoding a possible alternate or modified RNA polymerase beta prime subunit, predicted to have the expected subunit interaction domains but lacking most catalytic residues. A similar ORF was found in the Thioploca ingrica draft genome, but in no others. In both species they are immediately upstream of putative sensor kinase genes with nearly identical domain structures. In the marine Beggiatoaceae, a role for the TAACTGA repeats in translational regulation is suggested. More speculatively, the putative alternate RNA polymerase subunit could be a negative transcriptional regulator.